Epidemiology of Sindbis fever in South Africa and development of a real-time pan-alphavirus PCR assay for the detection of Sindbis and other medically important alphaviruses - Markotter, Wanda (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2013.